Improved Method for the Allelic Definition of C4A and C4B Polymorphism (HLA Class III). (May 2001) - Zorzetto, M.; Campo, I.; Cortelazzo, A.G.; Panelli, S.; Cuccia, M.
The polymorphism of the fourth component of human serum complement (C4) is well established at the proteinic level; at the DNA level in the analysis of C4A and C4B gene polymorphism, the PCR technique is not widely and routinely used because it is time consuming and still presents reproducibility problems. This is a serious problem because only PCR genotyping allows the establishment of Rodgers-Chido reverse antigenicity without the need for classical family segregation studies, whose samples are not always easy to obtain. The most commonly used protocol requires an initial PCR followed by nested amplification of all the products supposed positive or negative. The two reactions are set up using differing cycling conditions, primers, and magnesium chloride concentrations. We developed a simplified procedure to easily obtain reproducible results and used a single protocol for all reactions. Nested PCR is made using only the positive samples, so we decrease the number of samples to handle, the time spent for the work, and the reagents used for the reactions. Moreover, we increased the reproducibility of the experiments.